2021
DOI: 10.1002/smll.202101137
|View full text |Cite
|
Sign up to set email alerts
|

Conversion‐Alloying Anode Materials for Sodium Ion Batteries

Abstract: The past decade has witnessed a rapidly growing interest toward sodium ion battery (SIB) for large-scale energy storage in view of the abundance and easy accessibility of sodium resources. Key to addressing the remaining challenges and setbacks and to translate lab science into commercializable products is the development of high-performance anode materials. Anode materials featuring combined conversion and alloying mechanisms are one of the most attractive candidates, due to their high theoretical capacities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(79 citation statements)
references
References 263 publications
(351 reference statements)
0
79
0
Order By: Relevance
“…Although the conversion reaction could achieve a multiple electron reaction, it delivered a limited capacity above the average voltage of 0.6 V. Inspired by the reaction of alloying elements with sodium ions at lower voltages, the researchers found that the reaction voltage could be extended to a lower range to combine two different sodium storage mechanisms in one compound, thereby leading to the combined mechanism conversion-alloying (CA) reaction. [158] Similarly, the CA mechanism also suffers from sluggish reaction kinetics, large volume expansion, poor cycling stability, and so on. [159] The studies mainly focus on nanosizing the electrode materials to alleviate the volume expansion and to reduce the charge diffusion distance, thus promoting the cycling stability and rate capability.…”
Section: Conversion Reactionmentioning
confidence: 99%
“…Although the conversion reaction could achieve a multiple electron reaction, it delivered a limited capacity above the average voltage of 0.6 V. Inspired by the reaction of alloying elements with sodium ions at lower voltages, the researchers found that the reaction voltage could be extended to a lower range to combine two different sodium storage mechanisms in one compound, thereby leading to the combined mechanism conversion-alloying (CA) reaction. [158] Similarly, the CA mechanism also suffers from sluggish reaction kinetics, large volume expansion, poor cycling stability, and so on. [159] The studies mainly focus on nanosizing the electrode materials to alleviate the volume expansion and to reduce the charge diffusion distance, thus promoting the cycling stability and rate capability.…”
Section: Conversion Reactionmentioning
confidence: 99%
“…In the past few years, phosphorus-based materials, such as red phosphorus, metal phosphides and so on, have earned a lot of attention as negative electrode materials for NIBs. [21][22][23][24] Compared with other NIB negative electrode materials, such as carbon-based materials, [25][26][27] alloying-type materials, [28][29][30][31] transition metal oxides, 32 transition metal chalcogenides, 33,34 and so on, phosphorus-based materials show enormous superiority in terms of Na storage capacity based on an alloying or conversion reaction mechanism. 21 For example, red phosphorus possesses the largest theoretical specific capacity of B2600 mA h g À1 , and SnP 3 grabs the highest volumetricspecific capacity of 6890 mA h cm À3 in theory.…”
Section: Introductionmentioning
confidence: 99%
“…[11] At present, the most studied alloy materials are Sn, [12] Sb, [13] and P, [14] among which the theoretical specific capacity of element P can reach 2596 mAh g À1 . [15,16] These alloy-type anodes can provide high theoretical capacity due to the existence of multiple electron exchange reactions during the process of forming a binary alloy with sodium. However, this process is accompanied by serious electrode structure changes, and the volume expansion rates of Sn, Sb, and P are as high as 420%, 390%, and 440%, respectively.…”
mentioning
confidence: 99%
“…Thus, defect engineering is widely used to adjust the performance of alloy anodes. [15,19] Transition metal compounds are another type of high-capacity anode materials, including transition-metal oxides, sulfides, and selenides, because transition metals usually possess various oxidation states. [20,21] These transition metal compounds can be divided into two main categories.…”
mentioning
confidence: 99%
See 1 more Smart Citation